Dynamic stabilities of icosahedral-like clusters and their ability to form quasicrystals - Xiaogang Liang; Ilyar Hamid; Haiming Duan (AIP Advances, 2016)
The dynamic stabilities of the icosahedral-like clusters containing up to 2200 atoms are investigated for 15 metal elements. The clusters originate from five different initial structures (icosahedron, truncated decahedron, octahedron, closed-shell fragment of an HCP structure, and non-closed-shell fragment of an HCP structure). The obtained order of the dynamic stabilities of the icosahedral-like clusters can be assigned to three groups, from stronger to weaker, according to the size ranges involved: (Zr, Al, Ti) > (Cu, Fe, Co, Ni, Mg, Ag) > (Pb, Au, Pd, Pt, Rh, Ir), which correspond to the predicted formation ability of the quasicrystals. Thedifferences of the sequences can be explained by analyzing the parameters of the Gupta-type many-body inter-atomic potentials.